2016
DOI: 10.1021/acs.est.6b03657
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Musks in the Air and Water of the Lower Great Lakes: Spatial Distribution and Volatilization from Surface Waters

Abstract: Polycyclic musks (PCMs) are synthetic fragrance compounds used in personal care products and household cleaners. Previous studies have indicated that PCMs are introduced to aquatic environments via wastewater and river discharge. Polyethylene passive samplers (PEs) were deployed in air and water during winter 2011 and summer 2012 to investigate the role of population centers as sources of these contaminants to the Great Lakes and determine whether the lakes were acting as sources of PCMs via volatilization. Av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 38 publications
8
27
0
Order By: Relevance
“…69 In general, the median S 6 PCMs was $3 times higher at the 3 most urban sites, which were located at 0 km, 1 km, and 5 km from the city centre, than at the 3 most rural sites, which were located 40 km, 60 km and 80 km from the city centre. Our results are consistent with those of McDonough et al 41 who found significant correlations between population density and S 5 PCMs (ADBI, AHMI, ATII, HHCB, AHTN) in both air and water. We hypothesize that PCM sources supporting this gradient are the collective emissions from indoor air via building ventilation and from WWTPs during the treatment process.…”
Section: Outdoor Air and Soilssupporting
confidence: 93%
See 2 more Smart Citations
“…69 In general, the median S 6 PCMs was $3 times higher at the 3 most urban sites, which were located at 0 km, 1 km, and 5 km from the city centre, than at the 3 most rural sites, which were located 40 km, 60 km and 80 km from the city centre. Our results are consistent with those of McDonough et al 41 who found significant correlations between population density and S 5 PCMs (ADBI, AHMI, ATII, HHCB, AHTN) in both air and water. We hypothesize that PCM sources supporting this gradient are the collective emissions from indoor air via building ventilation and from WWTPs during the treatment process.…”
Section: Outdoor Air and Soilssupporting
confidence: 93%
“…Most studies on SMCs have focused on NMs and PCMs with fewer conducted on MCMs. 1,30,31 NMs and PCMs have been reported in indoor dust, 1,[32][33][34] indoor air, 32,35,36 outdoor air, [37][38][39][40][41][42] biota; 43-48 surface waters; 37,41,49-51 sea water, 37 sediments, 52 wastewater treatment plants (WWTPs); [53][54][55] drinking water, 56 human adipose tissue, 45,57,58 breast milk, 31,[59][60][61] and serum. 59,62 The potential for SMCs to undergo long-range transport is debatable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three deuterated polycyclic aromatic hydrocarbons (PAHs; fluorene-d 10 , pyrene-d 10 , and benzo[a] pyrene-d 12 ) were used as PRCs; average PRC losses were 97% for fluorene-d 10 , 61% for pyrene-d 10 , and 2% for benzo[a]pyrened 12 . Sampling rates (R s ) were calculated as detailed in previous studies (McDonough et al 2016a(McDonough et al , 2016b. In the WWTP deployments performed here, R s averaged 28.1 AE 4.4 L/d.…”
Section: Field Deploymentsmentioning
confidence: 99%
“…The ratio of target compound concentrations (at equilibrium) in the same passive sampler matrix between water and air was used to derive water-to-air gradients (chemical activity gradients), and corresponding gaseous air-water exchange fluxes (Liu et al 2016;McDonough et al 2016aMcDonough et al , 2016b. Because ratios were based on PFASs that had equilibrated (day 28 for WWTP effluents, days 16 and 32 for air polyethylene), the ratios were not influenced by R s or K PE values.…”
Section: Passive Sampler-based Water-air Gradientsmentioning
confidence: 99%